Evaluation of wound healing activity of Thunbergia laurifolia supercritical carbon dioxide extract in rats with second-degree burn wounds - Juthaporn Kwansang; Chandhanee Itthipanichpong; Wacharee Limpanasithikul (Wolters Kluwer Medknow Publications, 2015)
Thunbergia laurifolia Lindl (TL) has been traditionally used as an antidote, anti-inflammatory, and anti-drug addiction. This study investigated the burn wound healing activity of TL leaf extract (TLL) from supercritical CO 2 extraction in rats. The extract was prepared to 2.5%, 5%, and 10% gel (TLL gel). Rats were induced to second-degree burn wounds. They were randomly divided into six groups (six rats/group), which five groups were topically applied gel base, 1% silver sulfadiazine gel, 2.5%, 5%, and 10% TLL gel, respectively, for 14 days. Six untreated burn rats were used as the control group. The rats in each group were evaluated for wound healing rate, histological parameters, and wound collagen content. Rats treated with 10% TLL gel had a higher wound healing rate than rats in the control and untreated groups. An increase in collagen content, which indicates good regeneration of wound skin, was observed in the TLL treated rats from a pathological study by Masson's trichrome and collagen content assay. The results from this study suggest that T. laurifolia leaf extract obtained by supercritical CO 2 extraction promotes the recovery of wound skin by shortening the inflammation phase, increasing collagen content, and stimulating fibroblasts proliferation and migration in wound healing.